2013
DOI: 10.1186/1472-6882-13-145
|View full text |Cite
|
Sign up to set email alerts
|

Rhaphidophora korthalsii modulates peripheral blood natural killer cell proliferation, cytokine secretion and cytotoxicity

Abstract: BackgroundRhaphidophora korthalsii (Araceae) is a root-climber plant which has been widely used in Chinese traditional medicine for cancer and skin disease treatment. Previous reports have recorded its immunomodulatory effects on mice splenocyte and human peripheral blood. This study investigated the potential immunostimulatory effect of Rhaphidophora korthalsii on human PBMC enriched NK cell.MethodsPBMC was exposed to various concentrations of R. korthalsii extract and the T and NK cell population in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Extract from Rhaphidophora korthalsii enhanced the CD56/CD16 expression which leads to production of immunomodulatory cytokines, proliferation and killing ability of NK cells. 62 Other studies also demonstrated that chlorogenic acid and other plant phenolic compounds enhances macrophage phagocytic activity and NK cell activity. 63 , 64 Similarly, other in vitro studies revealed that chlorogenic acid enhances T-cell proliferation after induction with influenza virus antigen through production of IFN-γ and IFN-α.…”
Section: Discussionmentioning
confidence: 97%
“…Extract from Rhaphidophora korthalsii enhanced the CD56/CD16 expression which leads to production of immunomodulatory cytokines, proliferation and killing ability of NK cells. 62 Other studies also demonstrated that chlorogenic acid and other plant phenolic compounds enhances macrophage phagocytic activity and NK cell activity. 63 , 64 Similarly, other in vitro studies revealed that chlorogenic acid enhances T-cell proliferation after induction with influenza virus antigen through production of IFN-γ and IFN-α.…”
Section: Discussionmentioning
confidence: 97%
“…The main goal of Traditional medicine is to develop immunostimulators that are safer, entirely biodegradable and cost-effective in order to prevent diseases (7). Notably, several foods and dietary herbs have been consumed as formulations to improve the quality of life, and thus these can be employed as a valuable source of agents that can boost host immune responses by stimulating or suppressing both specific and non-specific immunity (8).…”
Section: Introductionmentioning
confidence: 99%
“…In Western high-income countries, the use of complementary and alternative medicine (CAM) in patients with cancer is as high as 91% (4,5). Immunostimulants can enhance the body's immunity, and one of the research directions of CAM is to find safe and effective immune stimulants that can be used in clinical practice to prevent diseases (6,7). Flor•Essence (FE) Tonics is a complex mixture of commercially available herbal extracts, and is sold as a dietary supplement and used by patients with cancer due to reports that it may aid in treating or preventing disease (8).…”
Section: Introductionmentioning
confidence: 99%